Pusat Pelatihan Badminton Di Sei. Pinang Dengan Pendekatan Arsitektur Kontemporer - Fikri Fikri; Gun Faisal; Wahyu Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The development of Badminton in Riau Province is developed compared to other islands. This is indicated by the achievements of Badminton athletes in Riau which are relatively minimal and rarely heard of achievement outside the region. So we need a Badminton training center that can accommodate all the activities of potential Badminton athletes in Riau. The design method that have been used was the results of the field survey, documentation, analysis of qualitative data and quantitative data. The design was designed according to the needs of badminton training that follows the standards. So it was expected to support athlete achievement. The Badminton training center in Riau will be planned in Sei. Pinang, Tambang Districts, Kampar Regency. Sei. Pinang selection because near to the capital of Riau Province, so it will be easily accessed because it is close to Bangkinang – Pekanbaru Street and also the availability of vast land to develop. The design of theme was used a Contemporary Architecture which applied the Thimoty principle, and is in accordance with comparative studies of contemporary buildings in the last 10 years. The concept in this design was used Blow In Badminton, which included 5 types of punches into the design of buildings and areas. The results of the design of the Badminton Training Center were divided into zones consisting of training zones, dormitory zones, parking zones, and recreation zones.Keywords: Sei. Pinang, Badminton Training Center, Contemporary Architecture